Three Special Forms of Epicycloid Profiles of Cam Rotors and Their Performance Analysis - Chen Qinghong; Li Yulong; Zhang Pingshan (Jixie chuandong)
Focusing on optimal profile construction of epicycloid cam rotors for pump, using the bisymmetric method and taking the rolling radius ratio as the structural variables, an equation of inner conjugate curve corresponding to epicycloid is derived; and then the different performance features of the pump under the three specific forms of hypocycloid, straight line segments and fixed-point as inner conjugate curves are analyzed. All results show that the effect of rolling radius ratio on pump performance is rapid in the front and slow in the back; the larger the rolling radius ratio is, the larger the shape factor is; and the better the lightweight effect is, the worse the flow ripple performance is; the special inner straight form provides the best overall performance for lightweight, flow ripple and easy machining; the special inner fixed-point form provides the maximum shape factor and easiest machining under any profile, etc. It is concluded that the inner straight form is an ideal profile structure for epicycloid cam rotors.